Healthy function and high valued utilization of edible fungi - Zhang, Yanrong; Wang, Dawei; Chen, Yuetong; Liu, Tingting; Zhang, Shanshan; Fan, Hongxiu; Liu, Hongcheng; Li, Yu (Food science and human wellness, 2021)
Edible fungi are large fungi with high added value that can be utilized as resources. They are rich in high-quality protein, carbohydrate, various vitamins, mineral elements and other nutrients, and are characterized by high protein, low sugar, low fat and low cholesterol. In addition, edible fungi contain a variety of bioactive substances, such as polysaccharides, dietary fiber, steroids, polyphenols, and most of these compounds have antioxidant, anti-tumor and other physiological functions. This review comprehensively discusses the bioactive components and functional characteristics of edible fungi (such as antioxidant, anti-aging, hypolipidemic activities, etc.). Then the recent developments and prospect in the high-valued utilization of edible fungi are discussed and summarized. The objective of this review is to improve the understanding of health-promoting properties of edible fungi, and provide reference for the industrial production of edible fungi-based health products.